2015
DOI: 10.1371/journal.pone.0122020
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Mucus Binds DC-SIGN and Inhibits HIV-1 Trans-Infection of CD4+ T-Lymphocytes

Abstract: Bodily secretions, including breast milk and semen, contain factors that modulate HIV-1 infection. Since anal intercourse caries one of the highest risks for HIV-1 transmission, our aim was to determine whether colorectal mucus (CM) also contains factors interfering with HIV-1 infection and replication. CM from a number of individuals was collected and tested for the capacity to bind DC-SIGN and inhibit HIV-1 cis- or trans-infection of CD4+ T-lymphocytes. To this end, a DC-SIGN binding ELISA, a gp140 trimer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…These results using freshly acquired human colorectal tissue and fresh as well as frozen/thawed semen showing lack of seminal enhancement of HIV-1 are similar to others utilizing cell lines, explants, and animal models. [6][7][8][9][10]17,34,35 In human colonic explants, these findings are similar to those by Dezzutti et al, 34 which showed no enhanced infection. Interestingly, rectosigmoid tissue is more prone than tonsillar and cervical tissue to R5 HIV-1 infection due to the high prevalence of available R5 cell targets and reduced chemokine blockade, 36,37 However, despite this increased gut lymphoid tissue infectibility, we did not see enhancement of viral replication early after HIV-1 exposure in fresh WS/SP (or frozen/thawed) conditions.…”
Section: Discussionsupporting
confidence: 89%
“…These results using freshly acquired human colorectal tissue and fresh as well as frozen/thawed semen showing lack of seminal enhancement of HIV-1 are similar to others utilizing cell lines, explants, and animal models. [6][7][8][9][10]17,34,35 In human colonic explants, these findings are similar to those by Dezzutti et al, 34 which showed no enhanced infection. Interestingly, rectosigmoid tissue is more prone than tonsillar and cervical tissue to R5 HIV-1 infection due to the high prevalence of available R5 cell targets and reduced chemokine blockade, 36,37 However, despite this increased gut lymphoid tissue infectibility, we did not see enhancement of viral replication early after HIV-1 exposure in fresh WS/SP (or frozen/thawed) conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, DC-SIGN mediated capture and internalization of HIV-1 particles by immature DCs alters the intracellular trafficking machinery, evades lysosomal degradation pathways and subsequently transfers virus to T-cells through infectious synapse283539484950. Several studies demonstrated that blocking of DC-SIGN significantly inhibited HIV-1 transmission from DC to T-cells5152. However, studies have also shown that DC-SIGN mediated internalized HIV-1 particles undergo degradation and subsequent presentation of HIV-1 antigen to T-cells535455.…”
Section: Discussionmentioning
confidence: 99%
“…Protein bands of interest were excised, alkylated and subjected to tryptic digestion according to standard protocols. Further mass spectrometry analysis was performed as described previously [64]. …”
Section: Methodsmentioning
confidence: 99%